RAPE CASES: GENRE AND RHETORICAL ANALYSIS OF CONTROVERSIAL MALAYSIAN LEGAL JUDGEMENTS - Maya Khemlani David; Neda Saeipoor; Mumtaz Ali (University of Kuningan, 2016)
Kachru and Smith (2008) emphasize that effectual communication in the context in which different varieties of world English are used, entails awareness of the varieties in use and their cultural, social, and ideational functions. Court reports by Malaysian Judges are part of legal documents, which may be considered as a genre. Investigating the linguistic details of these reports may be helpful in understanding the argumentative and persuasive strategies used in these judgments. The issue of rape and justice is an important concern inÂ society. The aim of this study is to investigate Malaysian judgment reports in the English language on rape cases from a linguistic perspective. Specifically, the aim of the study is to identify court of appeal judgment reports of rape cases as a Genre and to identify the moves used in this genre. The moves within the genre were identified by studying two controversial reports which showed that the judgments might suffer from relying on pathos argumentation in one critical move.Keywords:Â language, law, legal, judgment, Malaysia and courts